PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE ROTATING TRIO EXCHANGE TERHADAP PRESTASI BELAJAR PADA PEMBELAJARAN SEJARAH SISWA KELAS X IPA SMA NEGERI 5 BANDA ACEH - Afrita ,; Husaini ,; Nurasiah . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACTThe research entitled "The Influence of Cooperative Learning Model Type of rotating trio exchange on Student Achievement of Class X IPA SMA Negeri 5 Banda Aceh" is aimed to:   (1) to analyze the influence of cooperative learning model of rotating trio exchange type toward learning achievement on learning history of class X students of IPA SMA 5 Banda Aceh; and (2) to explain the factors that influence student's learning outcomes by using the rotating trio exchange type learning model on the learning achievement in the learning of the students' class  X IPA at SMA Negeri 5 Banda Aceh.The approach used in this research is quantitative and qualitative approaches with experimental research type. The population of this study is all students of class X IPA SMA Negeri 5 Banda Aceh which amounts to 150 students and consists of 5 classes, and the sample used is class X IPA3 consisting of 30 students as experimental class and X IPA4 consisting of 30 students as class control. Data collection techniques in this study using tests, documentation, and interviews. Based on normality test and homogeneity test which is based on post test of experiment class and control class, it can be concluded that the data in the experimental class based on the significant level obtained X2hitungX2tabel is 4,46 7,81. Then the data distribution of the final test score of the students in the experimental class is normally distributed. While the calculation of data in the control class in accordance with the significant level obtained X2hitungX2tabel is 2,07 7,81. For homogeneity test with two class test, the variance obtained from each group S12 = 68,23 and S22 = 49,10. After the data is processed based on the level of distribution F, then obtained Fhitung ≤ Ftabel = 1,38 ≤ 1,84. The result of t-test in analyzing the effect of learning result by using cooperative learning model of rotating trio exchange type obtained by t-test that is tcount = 2,82 whereas ttabel = 2,00, it means that thitung ttabel or 2,82 2,00. Accordingly, the test criteria are significant. This means that the use of cooperative learning model type rotating trio exchange effect on student learning outcomes on learning history. Factors that can affect student learning outcomes by using cooperative model type rotating trio exchange on learning history is the direct involvement of students in the learning process. Learning by using the rotating trio exchange model can improve students' learning interest to be better than before, and encourage students to be more active and cooperate in completing a task, the students not only become passive listeners of information submitted by teachers but involve students directly in teaching and learning process.Keyword: Cooperative Learning, Rotating Trio Exchange Learning Model, Learning Achievement.